PENGGUNAAN LOGO PERTAMINA OLEH PELAKU USAHA PENJUALAN BBM PERTAMINI TANPA IZIN PEMEGANG HAK MEREK (StudiKasus: Desa Tanjung Bungo Kecamatan Kampar Timur) - Saskia Pratiwi; Firdaus '; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Substantially, the notion of Intellectual Property Rights (hereinafterreferred to as IPRs) can be described as property rights arising or born due tohuman intellectual ability and IPR to discuss patents, trademarks and designs.Intellectual property rights are intangible objects resulting from humanintellectual activities which are expressed in a particular form of creation ordiscovery. Intellectual activity (creativity) is found in the fields of science, art andtechnology. In terms of law, it must be known that what is protected by law is IPR,not material in the form of IPR incarnationThe purpose of writing this thesis, namely; First, the impact of the use ofthe Pertamina logo used by business people without the permission of the brandrights holder, second, the efforts made by PT. Pertamina in overcoming the use ofthe logo used first.From the results of this study there are two main points that can bededuced: First, the impact of using the logo used by the first without the license orlicense of the holder of the trademark causes loss to PT. Pertamina, the first kioskowner and consumer. PT. Pertamina suffered material and immaterial losses. Inmaterial losses are experienced by PT. Pertamina with a significant cost due tothe accumulation of fuel oil caused by the kiosk, so that PT. Pertamina continuesto produce premium types of fuel oil. While immaterial loss is the seizure of brandrights that have been owned by PT. Pertamina which has been registered before.